Social marketing : doing well by doing good? a look into organizations? marketing communication campaigns on social issues in Finland - Lahtinen, Emmi (2010)
This study examined social marketing and related dimensions by looking at case campaigns of three Finnish organizations of the public, business and civic sector. Marketing on these sectors is about behavioral influence, but has diverse characteristics. The aims of the research were to clarify the multidimensional field of marketing applied to social issues, to find out the different dimensions, and to examine in which dimensions the case campaigns fit. Social marketing and related disciplines were studied as variants of marketing. A societal perspective and roles of mass media in creating social change were emphasized. The study could benefit the organizational communications and marketing practice by clarifying the field and giving insight in dimensions of social marketing and related campaigns. The cases were Lose Weight for Literacy (the National Institute for Health and Welfare), Drunk, You’re a Fool (the Federation of the Brewing and Soft Drinks Industry) and Make an environmental act, give up your prejudices (the Finnish Red Cross). The study had a qualitative approach exploring characteristics of campaigning on social issues. The research material included documents on the websites, which were analyzed by categorizing and using a method of content analysis. It was found that it is not possible to draw a strict line between the dimensions since some characteristics of the campaigns are overlapping and common. However, the environments, objectives and contents of the campaigns were seen to determine the categorization. The study concluded that organizations engaged in marketing applied to social issues could benefit of identifying the differences of the dimensions. Organizations could thus gain added value to their “doing well by doing good”. Future research on social marketing and related campaigning could concentrate on competition, interactive environments or media advocacy.